Cryptanalysis of some proxy signature schemes without certificates - Yap, Wun-She; Heng, Swee-Huay; Goi, Bok-Min (Springer Berlin Heidelberg, 2007)
The concept of proxy signature was introduced by Mambo et al. to delegate signing capability in the digital world. In this paper, we show that three existing proxy signature schemes without certificates, namely, the Qian and Cao identity-based proxy signature (IBPS) scheme, the Guo et al. IBPS scheme and the Li et al. certificateless proxy signature (CLPS) scheme are insecure against universal forgery.. More precisely, we show that any user who has a valid public-private key pair can act as. a cheating proxy signer and forge the proxy signature on behalf of the original signer at will, without obtaining the official delegation from the original signer.